The role of human resources management in managing organizational change in institutions:: A study of a group of institutions in the wilaya of Constantine - Boubartakh, Abdelkarim; Chanchouna, Mohamed (Journal of Human Sciences, 2021)
The purpose of this study is to identify the role of human resources management in managing organizational change, and to reach this, 15 questionnaires were distributed on public and private institutions as samples in the state of Constantine and then were analyzed using the SPSS software. The study revealed that despite the efforts made by the human resources department of these institutions to manage change, they do not keep pace with this emerging philosophy